2017
DOI: 10.1007/s11071-017-3367-7
|View full text |Cite
|
Sign up to set email alerts
|

On a systematic approach for cracked rotating shaft study: breathing mechanism, dynamics and instability

Abstract: We present a systematic approach to deal with the modeling and analysis of the cracked rotating shafts behaviour. We begin by revisiting the problem of modelling the breathing mechanism of the crack. Here we consider an original approach based on the form we give to the energy of the system and then identify the mechanism parameters using 3D computations with unilateral contact conditions on the crack lips. A dimensionless flexibility is identified which makes the application of the approach to similar problem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…In this article, we continue to improve the EDF − LMS approach to make it a more comprehensive and generic methodology in dealing with beams and shafts with cracks. We already have started the generalization of the approach in a recent article ((El Arem and Ben Zid, 2017)) where the problem was formulated to write the total elastic energy of the system as a function of the applied forces instead of bending moments. By giving an approximate formula of the extracted additional flexibility due to the crack breathing, we have shown that the procedure of identification could be skipped which would allow a significant effort saving for those who would have adopted the approach.…”
Section: Aim and Plan Of The Articlementioning
confidence: 99%
See 1 more Smart Citation
“…In this article, we continue to improve the EDF − LMS approach to make it a more comprehensive and generic methodology in dealing with beams and shafts with cracks. We already have started the generalization of the approach in a recent article ((El Arem and Ben Zid, 2017)) where the problem was formulated to write the total elastic energy of the system as a function of the applied forces instead of bending moments. By giving an approximate formula of the extracted additional flexibility due to the crack breathing, we have shown that the procedure of identification could be skipped which would allow a significant effort saving for those who would have adopted the approach.…”
Section: Aim and Plan Of The Articlementioning
confidence: 99%
“…In fact, in addition to being able to consider a crack of any shape, the possibility of having a crack located at any position along the shaft axis will be given. We are not limited by a crack at mid − span of the shaft like in (El Arem and Ben Zid, 2017). This becomes possible by constructing a CBFE that could be assembled with other beam finite elements (cracked or not) to model a beam or a shaft with cracks.…”
Section: Aim and Plan Of The Articlementioning
confidence: 99%
“…Dimarogonas's SERR crack model clearly reveals the impact of the regular opening and closing of the crack on rotor stiffness. However, the calculation process of solving the generated equation of motion of the cracked rotor is complex and not suitable for engineering practice [18]. In this paper, the model of cracked rotor is proposed by Papadopoulos and Dimarogonas [1], which can reveal changes in stiffness of the cracked rotor better, to create a crack model that can help in solving the equation of the rotor motion simply.…”
Section: Stiffness Model Of Cracked Rotormentioning
confidence: 99%
“…By using the inverse matrix of each softness matrix, the stiffness matrix KOP, KUC ,KHc are calculated, and the stiffness matrix Kc of cracked shaft element are obtained from formula (8). In formula (18), E, G, I, l and R are the elastic modulus, shear modulus, moment of inertia, length and radius of the axis, respectively.…”
Section: Stiffness Model Of Cracked Rotormentioning
confidence: 99%
“…In this article, we continue to advance a family of models and discussions we have started developing nearly twenty years ago at Electricité De France (EDF) and the Solid Mechanics Laboratory (LMS) ofÉcole Polytechnique in France. All these models belong to what we have called the EDF−LMS approach as described in [10]. It provides means to overcome the difficulties and imprecisions ([25, 5]) inherent to the first and oldest approach initiated in the 1970s by Dimarogonas and his coworkers and based on the linear fracture mechanics principles [26].…”
Section: Introductionmentioning
confidence: 99%